2017
DOI: 10.1680/jencm.16.00025
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic jumps and breaking bores: modelling and analysis

Abstract: In open channel flows, the transition from a rapid to fluvial flow motion is called a hydraulic jump. A related flow motion is a compression wave in a channel, also positive surge and bore. A key feature of hydraulic jumps and breaking bores is the rapid spatial and temporal deformations of the roller free-surface, in response to the interactions between entrained air bubbles and turbulent structures. The flow structure in the roller region remains a great research challenge because of large quantities of entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…mass flux direction (STOKER 1957, TRICKER 1965. Herein the air-water flow structures tended to be similar to gas-liquid structures observed in breaking hydraulic jumps (CHANSON 2011b, CHACHEREAU and CHANSON 2011, WANG et al 2017) and in the upper region of high-speed self-aerated flows (CAIN andWOOD 1981, CHANSON 1997a,b).…”
Section: Air-water Flow Patternsmentioning
confidence: 58%
See 1 more Smart Citation
“…mass flux direction (STOKER 1957, TRICKER 1965. Herein the air-water flow structures tended to be similar to gas-liquid structures observed in breaking hydraulic jumps (CHANSON 2011b, CHACHEREAU and CHANSON 2011, WANG et al 2017) and in the upper region of high-speed self-aerated flows (CAIN andWOOD 1981, CHANSON 1997a,b).…”
Section: Air-water Flow Patternsmentioning
confidence: 58%
“…It was shown that the entrapped air can be compressed, and resulting pressure shock waves can contribute to some substantial impact on structures (BREDMOSE et al 2009). The air entrainment in breaking bores has not been investigated to date, except for a few preliminary works (CHANSON 2009a,2016b, LENG and CHANSON 2015a, and a limited analogy with stationary hydraulic jumps (CHANSON 2009b, WANG et al 2017. CHANSON (2009aCHANSON ( ,2016b studied the atmospheric noise of breaking tidal bores, linking the low pitch sound of the advancing bore to a dominant frequency of collective oscillations of bubble clouds in the bore roller.…”
Section: Introductionmentioning
confidence: 99%
“…The fluctuations in bore celerity are large in both transverse and longitudinal directions, with ratio of standard deviation to mean value greater than unity. The bore roller toe perimeter constantly fluctuates with time and space, so it is not a straight line (CHANSON, 2016;WANG et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The second full-length paper (Wang et al, 2017) is devoted to bores and hydraulic jumps. Sketched by Leonardo da Vinci (Clark and Pedretti, 1968), observed in nature and utilised by engineers for a century, it might be thought that the hydraulic jump had yielded all its secrets some time ago.…”
mentioning
confidence: 99%
“…://dx.doi.org/10.1680/jencm.2017.170.1.1 ICE Publishing: All rights reserved most complete investigations of the average jump profile and length, Mossa andTolve (1998), Mossa (1999)), the research on this transition flow and its related flow motions, such as tidal bore or surge, is still relevant, as shown by Wang et al (2017) in their interesting paper. In fact, the authors show that the flow structure in the roller remains a great research challenge due to large quantities of entrained air, bubble turbulence interactions and the coupling between turbulent properties and free surface deformations.…”
mentioning
confidence: 99%